Potencial del diseño en los productos elaborados en guadua (2020)
The document presents young group research of Technology and Design intervention in research project called: Bamboo´s products design potential. This project aims to get necessary and relevant information about technological developments for to produce the production links from industrial design viewpoint. For that to supported by technological projecting that contribute to sustainable development based on graded and systematic inventory of products, It to identify abilities, skills in production techniques, objectual categories, processing factors, modernization and improvement of their potential designs in national and international markets.